CLINICAL PHARMACOLOGY OF METABOLISM-ACTIVATING AND CORRECTING DRUGS - Abubakirov Khamdambek Yusupovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the clinical pharmacology of metabolism-activating and correcting drugs, a heterogeneous group of agents designed to restore or optimize metabolic processes in pathological conditions. It provides an overview of drug classes, mechanisms of action, pharmacokinetics, clinical applications, and safety considerations. Special attention is given to the role of these agents in mitochondrial dysfunction, ischemia, metabolic syndrome, and neurodegeneration. The article highlights current evidence and emerging therapeutic strategies in both acute and chronic disease management.